New Insights Into Western Antarctic Peninsula Magmatism From Joint Inversion of UAV Magnetic and Gravity Data - Jordan, Tom A.; Lowe, Maximilian; Riley, Teal R. (Journal of geophysical research. Solid earth, 2025)
The Antarctic Peninsula is a unique sector of the circum‐Pacific continental margin arc where subduction ceased due to a series of ridge‐trench collisions, preserving a relatively un‐deformed magmatic arc. This region, therefore, has the potential to provide key insights into how subduction systems behave during their final stages. However, the remote nature of the region means that both geological and geophysical data coverage is often sparse, limiting the ability to interpret its tectonic evolution. Here we present a new analysis of gravity and magnetic data collected from a Windracers Ultra Uncrewed Aerial Vehicle (UAV). The survey targeted a 75 × 25 km region where the Antarctic Peninsula bends and magnetic signatures change, which has been attributed to the onshore influence of adjacent oceanic transform faults running approximately orthogonal to the Peninsula. Using joint inversion of magnetic and gravity data based on a “Variation of Information” approach, we show the region is dominated by two large intrusions, of likely granodiorite composition. Our data indicate little evidence for structural control on magma emplacement, however, coincident imagery suggests that after magma emplacement the region was subject to significant deformation approximately parallel to the Peninsula margin. We interpret these features in terms of the processes occurring as subduction ceased. Plain Language Summary The Antarctic Peninsula was formed over millions of years from a string of volcanoes and the underlying pools of magma, which turned to solid rock. The processes which control where and how these magmatic rocks formed are related to subduction, the process where dense oceanic crust is forced under the continental margin, releasing water, and triggering melting. Unfortunately, due to sparse data coverage and harsh working conditions the details of these important processes are poorly understood. Using a Windracers Ultra UAV, adapted for environmental science data collection, we collected high resolution gravity and magnetic measurements over an area where the pattern of magmatism was known to change. Using joint inversion of this data, where a computer model finds the rock properties which simultaneously match gravity and magnetic data, assuming magnetic and density (gravity) properties of the rocks are linked, we reveal the shape and type of the hidden rocks. These shapes and rock properties are interpreted, together with photographs of remote rocky islands, to give insights into the subduction processes occurring on the Antarctic Peninsula 20–50 million years ago. Key Points Gravity, magnetic and photographic data from a Windracers Ultra UAV is used to investigate the Antarctic Peninsula crustal structure Joint inversion shows ∼20% of the crust is formed of mafic intrusives emplaced c. 50 Ma, imagery shows subsequent trench parallel deformation Results reflect progressive shutdown of subduction impacting both crustal magmatism and deformation, likely via changing mantle flow